Leiomyoma of the esophagus: About 2 observations - Morelli, Raúl; Lucinschi, Alicia; Ferreyra, Ciro; López Susviela, Julio (Cirugía del Uruguay, 1986)
Observation of two cases of esophageal leiomyoma operated by authors is presented. This benign tumor of smooth muscle libre is the most frequent among esophagic tumors but its overall rate of frequency is very low. lt is often locat